Laelius Ashmead (Hymenoptera, Bethylidae) from Madagascar, with description of two new species - Barbosa, D. N.; Azevedo, C. O. (Zootaxa, 2009)
Laelius is recorded from the Afrotropical region for the first time, and two new species are described and illustrated. Laelius mekes sp. nov. is characterized by having the propodeal disc with seven carinae and the fore wing with long radial vein, and Laelius akares sp. nov. by having the propodeal disc with five carinae and the fore wing with short radial vein. A key to the species of Madagascar are also provided.